Osteocyte-derived extracellular vesicles mediate the bone-to-cartilage crosstalk and promote osteoarthritis progression - Na Liu; Yuze Ma; Wang Gong; Xiaoyan Shao; Tianshu Shi; Lan Li; Wenshu Wu; Xiang Chen; Yong Shi; Pan Zhang; Jiaquan Lin; Chengzhi Wang; et al. (Nature Communications)
Abstract Osteoarthritis is a common degenerative joint disease, in which mechanical overloading disrupts subchondral bone remodeling before cartilage degeneration and the osteocytes in the subchondral bone are mainly responsible for mechanosensing. However, their functional role in the early osteoarthritis is still unclear. Here we show that mechanical stress induces osteocytes in subchondral bone to secrete extracellular vesicles that accelerate cartilage metabolic dysregulation in patients with both sexes and male mice. The miR-23b-3p in extracellular vesicles promotes cartilage catabolism and inhibits anabolism by targeting OTUD4, disrupting mitophagy in chondrocytes. Inhibiting miR-23b-3p in osteocytes or chondrocytes reduces cartilage degeneration and osteoarthritis progression in male mice. Together, our findings highlight that osteocyte-derived extracellular vesicles mediate communication with chondrocytes and suggest miR-23b-3p as a potential therapeutic target for osteoarthritis.